Digital ulcers: should debridement be a standard of care in systemic sclerosis?. (May 2020) - Hughes, Michael; Alcacer-Pitarch, Begonya; Allanore, Yannick; Baron, Murray; Boin, Francesco; Bruni, Cosimo; Chung, Lorinda; Del Galdo, Francesco; Denton, Christopher P; Matucci-Cerinic, Marco
Summary: Digital ulcers are a serious, recurrent complication in patients with systemic sclerosis. They are often slow to heal and exquisitely painful. Local wound care, such as debridement of the wound bed, is an essential component in the management of digital ulcers in systemic sclerosis. However, digital ulcer debridement is not a standard of care, and there is substantial international variation in the use of this approach. In this Viewpoint, we discuss the assessment of the wound bed and different methods of debridement using the model of tissue management, infection and inflammation, moisture control, and wound edge or epidermal advancement, known as TIME. We highlight the challenges in standard practice and the need for research into local wound care for this type of ulceration, before suggesting a potential roadmap to develop a standardised approach to support ulcer debridement in systemic sclerosis. Debridement might be the missing component in optimising the management of digital ulcers and we propose that the approach should be rigorously investigated as a standard of care in this common complication of systemic sclerosis.